Prognostic Value of Molecular Subtypes in Pancreatic Cancer. Issue 4 (April 2017) - Bertucci, François; Birnbaum, David J.; Finetti, Pascal; Gilabert, Marine; Poizat, Flora; Raoul, Jean-Luc; Birnbaum, Daniel; Mamessier, Emilie
Abstract : Supplemental digital content is available in the text.